On the frequency shift resulting from the perturbation of an electromagnetic TM wave-mode by a small metallic cylinder in a resonant cavity. Part 1: Detailed theoretical treatment - Grosjean, Carl (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Véase archivo PDF